2010
DOI: 10.1007/s10549-010-1191-6
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in breast cancer characteristics and outcomes by race/ethnicity

Abstract: Purpose-Disparities in breast cancer stage and mortality by race/ethnicity in the United States are persistent and well known. However, few studies have assessed differences across racial/ethnic subgroups of women broadly defined as Hispanic, Asian, or Pacific Islander, particularly using more recent data.Methods-Using data from 17 population-based cancer registries in the Surveillance, Epidemiology, and End Results (SEER) Program, we evaluated the relationships between race/ ethnicity and breast cancer stage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
231
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(257 citation statements)
references
References 25 publications
20
231
2
Order By: Relevance
“…[16][17][18][19] Among the Asian subgroups, we observed that Japanese patients had better DSS rates than NHW patients and patients in other Asian subgroups, which is also consistent with previous reports. [19][20][21] We also observed that Hawaiian/Pacific Islander patients were more likely to be diagnosed with advanced disease (stage III or IV) and, as expected, had worse DSS rates than NHW patients and patients in all other Asian subgroups.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…[16][17][18][19] Among the Asian subgroups, we observed that Japanese patients had better DSS rates than NHW patients and patients in other Asian subgroups, which is also consistent with previous reports. [19][20][21] We also observed that Hawaiian/Pacific Islander patients were more likely to be diagnosed with advanced disease (stage III or IV) and, as expected, had worse DSS rates than NHW patients and patients in all other Asian subgroups.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with other studies demonstrating that Japanese patients are more likely to have ER-positive or PRpositive tumors than black or HW patients or patients in other Asian subgroups. 10,18,19,[22][23][24] The survival advantage of Japanese over NHW and other Asian subtypes slightly decreased after controlling for disease stage, which is consistent with a report by Pineda et al 20 Also, in agreement with previously published data, this survival advantage appears to be limited to the localized and regional stages. Once distant metastases are present (stage IV), Japanese do not fare as well as NHWs and other Asian subtypes.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Studies highlighting heterogeneity in breast cancer risk between Hispanic women underscore the importance of differences in country of origin, duration of residence in the United States, and acculturation in estimating the risk of breast cancer (10,(21)(22)(23). Further, there is evidence of genomic differences between Hispanic subgroups in the Unites States (24,25).…”
Section: Discussionmentioning
confidence: 99%